Double Take: Parallel Processing by the Cerebral Hemispheres Reduces the Attentional Blink. - Scalf, Paige E.; Kramer, Arthur F.; Narechania, Kunjan (Journal of Experimental Psychology. Human Perception & Performance, 2007)
Recent data have shown that parallel processing by the cerebral hemispheres can expand the capacity of visual working memory for spatial locations (J. F. Delvenne, 2005) and attentional tracking (G. A. Alvarez & P. Cavanagh, 2005). Evidence that parallel processing by the cerebral hemispheres can improve item identification has remained elusive. The authors used a novel variant of the attentional blink paradigm to show that the attentional blink is reduced if targets are divided between the hemispheres rather than directed to a single hemisphere. Parallel processing by the cerebral hemispheres can thus expand the capacity of processes involved in item identification. The authors also show that prior engagement of the attentional system may compromise the processing of items directed to the right visual field. This pseudoextinction may explain the failures of previous attempts to demonstrate that parallel processing can improve item identification (J. F. Delvenne, 2005; S. J. Luck, S. A. Hillyard, G. R. Mangun, & M. S. Gazzaniga, 1989). Reprinted by permission of the publisher.